Phase Plane Method for the Parameter Identification of Strongly Nonlinear Systems - Tang Jiashi (Shock and Vibration)
A phase plane method is presented for the parameter identification of strongly nonlinear systems. The phase trajectory equation is taken as the mathematical model and the system parameters are identified by using the optimum technique. The method can be applied to conservative and non-conservative systems. The value ranges of the parameters are not limited. All examples simulated by computer show that the efficiency and accuracy of this approach are very good.